TI_GERICHTE 52.2018.498 vom 26. September 2018 , Revoca di 12 mesi della licenza di condurre a seguito di un'infrazione grave (ebrietà) - TI Tribunale d'appello (2018)
Revoca di 12 mesi della licenza di condurre a seguito di un'infrazione grave (ebrietà)